Infections of Cryptococcus species induce degeneration of dopaminergic neurons and accumulation of α-Synuclein in Caenorhabditis elegans - Kitisin, Thitinan; Muangkaew, Watcharamat; Sukphopetch, Passanesh (Frontiers in Cellular and Infection Microbiology, 2022)
Cryptococcosis in the central nervous system (CNS) can present with motor declines described as Parkinsonism. Although several lines of evidence indicate that dopaminergic (DA) neuron degeneration and α-synuclein accumulation contribute to the hallmark of Parkinsonism and Parkinson’s disease (PD), little is known about cryptococcal infections associated with neuronal degeneration. In this study, the effects of Cryptococcus neoformans and C. gattii infections on dopaminergic neuron degeneration, α-synuclein accumulation, and lifespan in Caenorhabditis elegans were investigated. The results showed that cryptococcal infections significantly (P<0.05) induced DA neuron degeneration similar to a selective cathecholamine neurotoxin 6-hydroxydopamine (6-OHDA) in C. elegans (BZ555 strain) when compared to mock infected controls. Cryptococcal infections also significantly (P< 0.05) induced α-synuclein aggregation in C. elegans (NL5901 strain). Moreover, lifespan of the infected worms was significantly decreased (P<0.0001). In conclusion, DA neurodegeneration and α-synuclein accumulation are associated with lifespan reduction during cryptococcal infection in C elegans.